Association of COMT and COMT-DRD2 interaction with creative potential - Zhang, Shun; Zhang, Muzi; Zhang, Jinghuan (Frontiers in Human Neuroscience, 2014)
Several lines of evidence suggest that genes involved in dopamine (DA) transmission may contribute to creativity. Among these genes, the catechol-O-methyltransferase gene (COMT) and the dopamine D2 receptor gene (DRD2) are the most promising candidates. Our previous study has revealed evidence for the involvement of DRD2 in creative potential. The present study extended our previous study by systematically exploring the association of COMT with creative potential as well as the interaction between COMT and DRD2. Twelve single nucleotide polymorphisms (SNPs) covering COMT were genotyped in 543 healthy Chinese college students whose creative potentials were assessed by divergent thinking tests. Single SNP analysis showed that rs174697 was nominally associated with verbal originality, two SNPs (rs737865 and rs5993883) were nominally associated with figural fluency, and two SNPs (rs737865 and rs4680) were nominally associated with figural originality. Haplotype analysis showed that, the TCT and CCT haplotype (rs737865-rs174675-rs5993882) were nominally associated with figural originality, and the TATGCAG and CGCGGGA haplotype (rs4646312-rs6269-rs4633-rs6267-rs4818-rs4680-rs769224) were nominally associated with figural originality and verbal flexibility, respectively. However, none of these nominal findings survived correction for multiple testing. Gene-gene interaction analysis identified one significant four-way interaction of rs174675 (COMT), rs174697 (COMT), rs1076560 (DRD2) and rs4436578 (DRD2) on verbal fluency, one significant four-way interaction of rs174675 (COMT), rs4818 (COMT), rs1076560 (DRD2) and rs4648317 (DRD2) on verbal flexibility, and one significant three-way interaction of rs5993883 (COMT), rs4648319 (DRD2) and rs4648317 (DRD2) on figural flexibility. In conclusion, the present study provides nominal evidence for the involvement of COMT in creative potential and suggests that DA related genes may act in coordination to contribute to creativity.